PENGARUH METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS IV DI SD N 79 / VI SERINGAT KABUPATEN MERANGIN - Aprimadedi; Zahara Marylia; Amril (STKIP Subang, 2023)
The problem that forms the background of this study is the low Indonesian speaking skills of class IV students at SDN 79 Seringat in Indonesian content in learning the theme 8 sub-themes 1. In an effort to overcome this problem, it is necessary to apply the role playing method to Indonesian content. The purpose of this study was to determine the effect of the role playing method on the Indonesian speaking skills of students in the Indonesian language content of class IV SDN 79 Seringat. This study used a Pre-Experimental design with a One-Group Pretest-Posttest Design. The population in this study were all students in class IV at SDN 79 Seringat, while the sample used was students in class IV at SDN 79 Seringat, which consisted of 15 students. The sample in this study was taken using a saturated sampling technique. The data collection technique was taken using an observation sheet, the results of the observation data were calculated and compared based on the analysis with the validity test using the size validity test with the same sample (pairs) the result was 12.669. Based on these values, it can be seen that the value of tcount > ttable (12.669 > 2.145), then there is a difference between the pretest and posttest. the reliability test using the method repeated technique obtained a result of 0.894. Based on these values, it can be seen that the r-statistic value > from the r-table value of moment products (0.894 > 0.054), then there is a significant difference between X and Y. Then test the hypothesis through Excel 2010 at the level of 0.05. The results of the analysis of observational data from hypothesis testing on paired t-test of two sample means with a significance level of 0.05 show the results of sig. P(T<=t) two-tail is smaller than a or in the equation 0.000 <0.05, then H0 is rejected. Based on the results of the analysis of the observational data, it can be concluded that the role playing method has a significant influence on Indonesian Speaking Skills in the Indonesian language content of Grade IV students at SDN 79 Seringat, Merangin Regency.